The Relationship Between Room Sanitation, Vector Presence, Food Hygiene, and Waste Management and the Sanitary Condition of Passenger Ships Docking at Tobelo Port - Roberto Cabu; Engganis Dadere (BIOSAINSTEK, 2026)
Passenger ships require continuous sanitation control because their enclosed spaces, passenger movement, food services, waste production, and vector risks may affect public health. This study examined factors associated with the sanitary condition of passenger ships docking at Tobelo Port, including room sanitation, vector presence, food sanitation, and waste management. A quantitative cross-sectional study was conducted from March to April 2026 involving five passenger ships and 43 crew members selected by total sampling. Data were obtained through direct observation and structured interviews. The analysis was performed descriptively and continued with logistic regression using a significance level of p < 0.05. The findings indicated that room sanitation was the factor most consistently associated with ship sanitary condition, with p = 0.01 in all observed ships. Meanwhile, vector presence, food sanitation, and waste management showed significant associations only on certain ships, reflecting differences in daily sanitation practices and operational management. Although waste management had the weakest statistical association, it remains essential to reduce environmental contamination and health risks. Therefore, sanitation improvement at Tobelo Port should focus on maintaining room sanitation, strengthening vector control, improving food handling practices, and ensuring safer waste management through routine inspection, crew guidance, and risk-based supervision.